2019
DOI: 10.31744/einstein_journal/2019rc4668
|View full text |Cite
|
Sign up to set email alerts
|

Peri-prosthetic infection in the postoperative period of endovascular abdominal aorta aneurysm repair: treatment by percutaneous drainage

Abstract: Endovascular aneurysm repair is an established technique for treating many infrarenal aortic aneurysms. Infection is one of the most serious complications of this technique, and although percutaneous treatment has been well established for intra-abdominal collections, its use to treat peri-prosthetic fluid collections has not been well determined. In this article we describe a small series of three patients who were treated with percutaneous drainage, with good clinical and imaging responses. Percutaneous drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Outside of case reports, available literature on percutaneous management of AGI is limited to a few small case series with a total of less than 50 patients (Table 3). [6][7][8][9][10] Our experience favorably compares to the majority of available literature with no reported in-hospital mortality or 30-day mortality and no drain-related complications. Additionally, 67% of patients were alive at a median follow-up of 2 years post-drainage placement; with only 2 deaths attributable to AGI sequelae (22.2%).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Outside of case reports, available literature on percutaneous management of AGI is limited to a few small case series with a total of less than 50 patients (Table 3). [6][7][8][9][10] Our experience favorably compares to the majority of available literature with no reported in-hospital mortality or 30-day mortality and no drain-related complications. Additionally, 67% of patients were alive at a median follow-up of 2 years post-drainage placement; with only 2 deaths attributable to AGI sequelae (22.2%).…”
Section: Discussionsupporting
confidence: 56%
“… 1 , 2 Several small case series have described successful percutaneous drain placement in the context of AGI. 4 , 6 - 9 At our institution, in select patients, we have utilized percutaneous drainage of AGI as a bridge to surgical explantation or alternatively as definitive treatment combined with antibiotic therapy. We aim to identify safety, efficacy, and clinical outcomes of percutaneous drainage of aortic/periaortic sac infections following either open or endovascular repair of thoracic and/or abdominal aortic aneurysmal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lower limb revascularization, data on mortality, re-intervention, and major and minor amputation rates are essential to inform therapeutic decisions in terms of surgical technique, postoperative care, and rehabilitation. (36,37) Regarding aortic repair, a highly complex surgery with severe potential complications, (38) knowing the outcomes is essential in reducing postoperative mortality. For example, in the United Kingdom, after an epidemiological analysis revealed that the local mortality rate following elective AAA open repair was worse than that in neighboring countries, an initiative was implemented to evaluate and change perioperative care, especially anesthetic care.…”
Section: ❚ Center Auditmentioning
confidence: 99%